Salivary β‐galactosidase, halitosis parameters in periodontal health and disease, and their changes after periodontal treatment. (11th June 2021) - Aliyev, B; Pasaoglu, O; Pasaoglu, H; Gungor, K; Guner, E; Celik, B; Tuter, G
Abstract: Background: In this study, we aimed to evaluate the salivary β‐galactosidase and Halimeter values (HMV), organoleptic scores (OLS) and Winkel tongue coating index (WTCI) in periodontal health and periodontitis (P), and also their changes after phase I periodontal therapy and tongue cleaning. Methods: The participants were separated as follows: 25 P with halitosis (Group 1), 25 P without halitosis (Group 2) and 25 healthy controls (Group 3). Periodontal recordings, HMV, OLS and WTCI scores were recorded, and whole saliva β‐galactosidase levels were measured colorimetrically in the samples at baseline and 1 month after the therapy. Results: The baseline values of HMV, OLS, WTCI and salivary β‐galactosidase levels were significantly higher in Group 1 than in Group 2 ( P < 0.05). There was a statistically significant decrease in periodontal recordings, HMV, OLS, WTCI and salivary β‐galactosidase levels in all P patients by the therapy ( P < 0.05). However, major reductions in halitosis measurements and saliva enzyme levels were observed in Group 1 after the treatment. Conclusion: Our results showed that salivary β‐galactosidase was associated with halitosis parameters and phase I periodontal therapy played an important role to reduce this enzyme level and halitosis parameters in P.